THE EFFECT OF STRESSORS (SOURCES OF WORK STRESS) AND WORK MOTIVATION ON WORK PERFORMANCE AT THE BRI UNIT OF PADANGMATINGGI PADANGSIDIMPUAN - Hasibuan, Deby Pratiwi; Siregar, Onan Marakali (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2022)
This research seeks to reveal the relationship between stressors (sources of work stress) and work motivation on work performance at the BRI unit of PadangMatinggi Padangsidimpuan. Work motivation will be studied partly and concurrently in relation to Stressors. This research employs a quantitative methodology with an associative approach, sampling thirty workers. This research used a saturated sample for its sampling procedure. Data was collected from respondents through the use of Likert-scale questionnaires that were sent to them directly. Instrument test of reliability validity, classical assumption test, and hypothesis test employing multiple linear regression analysis in SPSS constituted the data analysis approach. The results of this study indicate that partially, Stressors have a positive and significant effect on work performance and work motivation has a positive and significant influence on work achievement. Simultaneously, Stressors and work motivation have a positive and significant effect on work achievement. The results of the coefficient of determination test showed that R was 0.757 or 75.7%. The Adjusted R Square value is 54.2% while the remaining 45.8% is influenced by other variables not explained in this study. This shows that the higher the Stressor and work motivation felt by the employees, the work achievement of the employees of BRI Unit of Padangmatinggi, Padangsidimpuan will increase.